The quantitative research of landscape color: A study of Ming Dynasty City Wall in Nanjing. Issue 3 (14th March 2018) - Cheng, Yuning; Tan, Ming
Abstract: Due to the richness of landscape color, together with the complexity of the environment, the objective measurement of landscape color has become very difficult. The evaluation and design of landscape color has depended on the perceptual experience acquired by the designer's eyes over a long period of time without objective and scientific basis in quantitative aspects. Therefore, development of a protocol for evalutation of environmental color change based on instrumental measurement in order to realize the quantitative expression of landscape color and to describe objectively the visual effect of the landscape color composition objectively, is a crucial factor in the landscape design process. This report takes the quantitative analysis of the color of the Ming Dynasty City Wall in Nanjing as a case study. Through the classification of color measurements, the on‐site investigation and sampling analysis in the landscape field, and the categorization and selection of the environment variables that influence the visual effect of color, this article illustrates the value and significance of the quantitative expression in the landscape color research to make landscape color effect more scientific, objective, and effective.